Psychiatric analysis of treatment-resistant allergic rhinitis and evaluation of the effects of antidepressant use - Orhan Uçal, Yusuf; Deniz Tansuker, Hasan; Bakım, Bahadır; Yıldırım, Ömürsen; Sözen, Esra; Uslu Coşkun, Berna (ENT Updates, 2017)
Objective: We evaluated the incidence of psychiatric disorders in patients with allergic rhinitis (AR) and assessed the effects of the use of antidepressants on symptoms when they are included in the treatment regimen of patients with AR who are resistant to AR treatment. Methods: A total of 49 patients who were resistant to the treatment for AR and who did not accept the option of immunotherapy were included in the study. Thirty-eight of the 40 patients were advised to take the antidepressant sertraline; however, only 21 of them agreed to use the medication while 17 of them refused. The 21 patients who agreed to begin the antidepressant were also advised to undergo AR treatment with desloratadine once per day and intranasal mometasone furoate once per day (Group 1). The patients who refused to use the antidepressant were advised to begin the AR treatment (Group 2). Symptom scoring for AR was again performed for all patients 6 weeks after treatment. The Psychological Symptom Checklist-90 (SCL-90), Beck Depression Inventory (BDI), and State-Trait Anxiety Inventory (STAI TX I and TX II) were performed on the patients in the company of a psychiatrist. Results: The post-treatment nasal and non-nasal symptom scores in Group 1 were significantly better than the pretreatment scores for any of the seven symptoms (p=0.000). No significant correlation was found between the AR symptom scores and the average SCL-90 general symptom score, the SCL-90 subscale scores, the total BDI scores, and the STAI scores (p>0.05). Conclusion: This study suggests that the use of antidepressants diminishes the allergic symptoms in patients with treatment-resistant AR since psychosomatic factor is of great importance in the patient population of AR.